Mobile device use when caring for children 0-5 years: A naturalistic playground study - Mangan, E.; Leavy, J.; Jancey, Jonine (Australian Health Promotion Association, 2018)
Issue addressed: Over the past decade, mobile device use has increased significantly. Adults are now using their mobile device whilst undertaking a range of work and social activities. This naturalistic study aimed to understand parents/carers' use of mobile devices and their associated beliefs about mobile device use whilst caring for children aged five and younger in playgrounds. Methods: A mixed methods approach was used to collect quantitative and qualitative data from parents/carers. Data were collected by observations (n = 50) and interviews (n = 25) in playgrounds on the North Coast of New South Wales, Australia. Results: Of the 50 observed parents/carers, 76% (n = 38) used their mobile device, with usage time extending to 17.2 minutes of the 20 minute observation period. Text-/type-related mobile device use was most often used (69.6%), followed by voice-related (23.7%) and camera-related mobile device use (6.7%). The 25 interviewed parents/carers beliefs on mobile device use were centred on three themes: diversity of mobile device use, child relationships and mobile device use and the physical environment and mobile device use. Conclusion: This study adds to the limited research into parent/carer mobile device use, which has become an integral part of peoples' lifestyle. However, research is required to better understand how parent/carer mobile device use may impact on child supervision and interaction. So what?: Mobile device use is increasing. We need to better understand its public health impact.